Validation Psychometrical analysis of Sexual Machism Scale (EMS-Sexism-12) among university students from Arequipa, Peru - Julio Cesar Huamani-Cahua; Estefany Cecilia Ojeda-Flores; Walter L Arias-Gallegos; Ferdinand Eddington Ceballos Bejarano; José Manuel Calizaya López (Interacciones)
Background: Sexual masochism is a form of gender discrimination based on beliefs, stereotypes and attitudes that limit autonomy and devalue individuals based on their gender. Objective: To determine the internal structure validity and reliability of the EMS-Sexism-12 to measure sexual machismo in the Peruvian population. Method: The study used an instrumental design with a convenience sample of 2470 students from a public university in Arequipa, Peru. The sample consisted of 50% men (M = 20.53; SD = 2.64) and 50% women (M = 19.95; SD = 2.27), representing engineering and social science disciplines. The instrument used was the Sexual Machismo Scale (EMS-Sexism-12), originally constructed and validated in Mexico. Results: The data were analysed using CFA and the WLSMV estimator along with polychoric correlation matrices in the open-source software Rstudio. The analysis revealed a unidimensional model with good fit indices for both men (CFI = .924, TLI = .907, SMRM = 0.069) and women (CFI = .936, TLI = .922, SMRM = 0.051). Furthermore, evidence of internal consistency reliability was observed for men and women, respectively (ω = .969; ω = .897). Gender-specific norms are included for reference. Conclusions: The sexual machismo scale shows evidence of similar validity and reliability with the same items in men and women from Arequipa, Peru.